ZAKAT: CONCEPT AND IMPLICATIONS TO SOCIAL AND ECONOMIC (ECONOMIC TAFSĪR OF AL-TAWBAH:103) - Al-Faizin, Abdul Wahid; Insani, Taqiyah Dinda; Herianingrum, Sri (Bank Indonesia, 2018)
One of the most used methods by Ulamā’ to find the laws and wisdoms from Quran is a tafsīr method. This paper try to find and analyze the concept from sūrah al-Tawbah: 103 - ayah with the more general content related to the concept and function of zakat – by using the tafsīr method and how the implication of zakat for the social and economic equality is. The method used in this paper is a qualitative method by using content analysis that combines tafsīr bi al-ra’yi with tafsīr bi al-ma’thūr. By using economic interpretation, the result shows that zakat should be an obligatory system and its management must be done centrally by the government. In this case Baznas can be a representation of the government to perform the task. The study also found that there are two implications of the zakat mentioned in sūrah al-Tawbah: 103. First, التطهير (purification) through which zakat is able to provide social implications of tranquility, security, and harmony. Secondly, التزكية (holy, blooming, blessing and praise) through which zakat has economic implications both in micro aspects (increase in quantity in the economic curve) and macro (increased investment and depletion of poverty and unemployment).